Biochemical Characterization of the Brain Hippocampal Areas after Cerebral Ischemia-Reperfusion Using Raman Spectroscopy. Issue 10 (October 2018) - Jung, Gyeong Bok; Kang, Sung Wook; Lee, Gi-Ja; Kim, Dohyun
Cerebral ischemic stroke is one of the most common neurodegenerative conditions characterized by cerebral infarction, death of the brain tissue, and loss of brain function. Cerebral ischemia-reperfusion injury is the tissue damage caused when blood supply begins to the tissue after a period of ischemia or poor oxygen supply. In this study, we preliminarily investigated the biochemical changes in the brain hippocampal area, CA1, resulting from ischemia reperfusion and neuronal nitric oxide synthase (nNOS) inhibitor treatment in rats using Raman spectroscopy. A drastic spectral change was observed in the ischemia-reperfusion brain tissue; a strong dependency between the intensity of certain Raman bands was observed at the amide positions of 1276 and 1658 cm −1 and at the lipid positions of 1300 and 1438 cm −1 . The spectrum of nNOS inhibitor-treated brain tissue was similar to that of the normal brain tissue, indicating that the nNOS inhibitor could protect the brain against excessive production of NO and biochemical processes dependent on it. Principal component analysis (PCA) precisely identified three classes of tissues: normal; ischemic; and nNOS inhibitor-treated. Therefore, we suggest that quantitative analysis of the changes in the brain tissue by using Raman spectroscopy with multivariate statistical technique could be effective for evaluating neuronal injury and drug effects.